2012
DOI: 10.1258/vasc.2011.cr0294
|View full text |Cite
|
Sign up to set email alerts
|

Infection of endovascular abdominal aortic aneurysm stent graft after urosepsis: case report and review of the literature

Abstract: Infection of endovascular abdominal aneurysm stent grafts is an uncommon but known complication. Inoculation with bacteria of the endovascular abdominal aneurysm stent graft during the actual implantation, in the periprocedural hospitalization or later due to an aortoenteric fistula, has been described in the literature. We report a case of endovascular abdominal aortic aneurysm stent graft infection occurring 40 months after implantation in a patient doing well up to an episode of urosepsis. In conclusion, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the literature, potential risk factors for endograft infection include adjunctive endovascular procedures during the primary implantation, immunesuppression, the treatment of pseudoaneurysms, and infected central venous catheters. [19] Veger et al [20] discovered that prophylactic administration may decrease the likelihood of bacteremia before stent graft insertion. Additionally, the authors also postulated that poor intraluminal healing of stent grafts, as observed in several explant studies, may result in higher susceptibility to episodes of bacteremia than for patients for whom prosthetic vascular grafts were inserted during open repair.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, potential risk factors for endograft infection include adjunctive endovascular procedures during the primary implantation, immunesuppression, the treatment of pseudoaneurysms, and infected central venous catheters. [19] Veger et al [20] discovered that prophylactic administration may decrease the likelihood of bacteremia before stent graft insertion. Additionally, the authors also postulated that poor intraluminal healing of stent grafts, as observed in several explant studies, may result in higher susceptibility to episodes of bacteremia than for patients for whom prosthetic vascular grafts were inserted during open repair.…”
Section: Discussionmentioning
confidence: 99%
“…This disruption leads to a false aneurysm formation, sepsis, graft enteric fistula, hemorrhage, limb loss, or death 2 , 19. Late graft infections may also occur due to bacterial seeding on the luminal surface after bacteremia caused by dental extraction or dental foci manipulation, urinary tract manipulation, urosepsis, or endovacscular invasive procedures 2 , 19 , 25…”
Section: Discussionmentioning
confidence: 99%